Active Ingredients and Natural Raw Materials Used in Foot Care in Diabetic Patients—A Literature Review - Aleksandra Krawiec; Olga Czerwińska-Ledwig; Bartłomiej Kita; Anna Piotrowska (Cosmetics, 2023)
Diabetic foot syndrome is the leading cause of limb loss due to non-healing ulcers. Repeated injuries, abnormal foot loads, and ischemia lead to ulcers. Poor shoe selection and inadequate care worsen the situation. Lack of patient education contributes to bacterial infections, tissue necrosis, and amputation. Vigilant observation and regular care can reduce wound size and prevent new wounds. Cleansing, infection control, and pressure relief are crucial in diabetic foot treatment. In this review, the effect of selected active ingredients and natural raw materials used for topical application in the care of diabetic foot was analyzed. The main focus used was on ingredients of natural origin—research studies utilizing emollients, humectants, plant extracts, and animal-derived ingredients were discussed. In addition, research studies on the application of nanomaterials, ozone and stem cells are also discussed. The cosmetics industry and manufacturers of podiatric products play a vital role in diabetic care. They should prioritize proper formulation, optimal ingredient doses, and skin microbiome control. Educating diabetics and using cosmetic products with self-massage elements can reduce the risk of hard-to-heal ulcers.